Determining genetic variability of traits in backcross populations of sweet corn (Zea mays L. var. Saccharata) - Rathinavel, Krishnakumar; Chandran, Sarankumar; Manoharan, Bharani; Doraiswamy, Uma; Rajasekaran, Ravikesavan; Zachariah, John Kenedy; Natesan, Senthil (Journal of Phytology, 2022)
To understand the nature of the traits in breeding programme, knowledge on heritability, genetic advance and genetic variability are inevitable. The paramount aim of the present study was to estimate the heritability, genetic advance and genetic variability of the backcross and selfed population of sweet corn and β-carotene rich inbred combinations viz., USC1-2-3-1× UMI1230β+ and SC1107× UMI1230β+ in order to identify the plants with superior trait combinations. The study involved the recording of fourteen biometrical traits in both the cross combinations which revealed that in backcross and selfed populations, the phenotypic coefficient of variation (PCV) was found to be greater than the genotypic coefficient of variation (GCV) indicating the probable influence of environment in the expression of the traits evaluated. High heritability was recorded for the important trait single plant yield in both the cross combinations of BC2F2 generation. Further, high heritability and high genetic advance as percent of mean was noticed for the traits like plant height, cob length, leaf length and single plant yield under both the cross combinations of BC2F2 generation indicates the governance of additive genes in expression of these traits. Hence, selection for these traits would be effective in developing a genotype with improved yield.